From the Traditional to the Diverse: Creative Research as a Path to Investigate Literature, Notes Based on Experience - Chávez Cervantes, Ángela María (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The Pedagogical and Technological University of Colombia (UPTC) offers the Masters in Literature as one of its postgraduate programs, and this program has a research line in Creative Research . This article is a result of my reflection on this research methodology as a student of this Masters program. For this purpose, we trace the discussion and conceptual steps taken by different universites and knowledge va - lidation institutions in Colombia to define and legitimize creative research in the Colombian academic context. The practice of creative writing is the result of a research process